2022
DOI: 10.1177/10760296221131801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Thromboelastography in Acute Ischemic Stroke

Abstract: Acute ischemic stroke (AIS), characterized by high morbidity and mortality, has imposed a considerable burden on society. Despite rapid development in the treatment of AIS, there is still a high risk of recurrence. Furthermore, there is a time delay in waiting for the results of conventional coagulation tests in candidate patients for intravenous thrombolysis therapy. Heterogeneous responses to antiplatelet, intravascular thrombolysis, and endovascular therapies also worsen the situation. Thromboelastography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…The human medical literature indicates that changes in TEG are consistent with hypercoagulability in patients with ischemic stroke and may have some predictive value for classifying ischemic vs hemorrhagic strokes. [21][22][23] Patients diagnosed with ischemic CVAs were more likely to have TEG changes consistent with hypercoagulability, and certain parameters (K value, angle) reflected severity of cerebral infarction. 21 Additionally, parameters such as an R value <5 minutes were associated with increased risk of hemorrhagic transformation of acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human medical literature indicates that changes in TEG are consistent with hypercoagulability in patients with ischemic stroke and may have some predictive value for classifying ischemic vs hemorrhagic strokes. [21][22][23] Patients diagnosed with ischemic CVAs were more likely to have TEG changes consistent with hypercoagulability, and certain parameters (K value, angle) reflected severity of cerebral infarction. 21 Additionally, parameters such as an R value <5 minutes were associated with increased risk of hemorrhagic transformation of acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…People diagnosed with cerebral hemorrhage most often had evidence of a hypocoagulable state, although some individuals had results suggesting a hypercoagulable state 21 . Thromboelastography also may be used to guide and monitor response to thrombolytic, antiplatelet, and anti‐coagulant treatment 23 . We were unable to assess for an association between hemorrhagic CVAs and hypocoagulability because no dogs had TEG results consistent with hypocoagulability, and TEG changes in response to anti‐stroke treatment also were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are effects on a number of parameters, mainly including prolonged R time, prolonged K time, and reduced maximum amplitude [127][128] Maximum controlled study has shown that, for patients experiencing intracerebral hemorrhage while on anti-thrombotic therapy, resuming antiplatelet therapy has only a minor impact on the risk of recurrent intracerebral hemorrhage. However, the secondary prevention benefits of antiplatelet therapy far outweigh the risks of intracerebral hemorrhage [132] .…”
Section: Tegmentioning
confidence: 99%
“…Acute ischemic stroke might be associated with hypercoagulability in approximately 30 to 40% of these patients. 1 2 This association could be explained by the fact that the exposure of collagen in damaged vessels triggers a cascade of coagulation factors which therein forms the emboli that can occlude cerebral arteries. 3 Hypercoagulability could also be involved in early neurological deterioration which occurs in approximately 20 to 30% of patients following acute ischemic stroke.…”
mentioning
confidence: 99%